"Senhora presidente, esta é uma carta pessoal": o gênero como prática social e situada - Bortolini, Fernanda Lopes (2020)
This research, posted on study line ‘Constitution and Interpretation of the Text and Discourse’ of Program of Postgraduate in Letters, of the University of Passo Fundo, has as theme the study of the discourse genre as a social practice, inserted in the discursive interaction and consisting of dialogic relations that generate meaning, and, consequently, established as a discursive event. The principal objective is to understand the discursive event - the letter from then Vice-President Michel Temer, written to the former president, Dilma Rousseff, and released to the press on December 7, 2015, from the mobilization of theoretical notions and principles from the linguistic perspective and dialogism, constitutive of the architecture of the Dialogic Theory of Discourse and the Theory of Genres of Discourse. Looking for it, the work addresses in the theoretical perspective of the Bakhtin Circle, based on the writings of Bakhtin (2010 [1975]; 2013 [1929]; 2016 [1952-1953]), Volóchinov (2017 [1929]), Medviédev (2016 [1928]). The corpus is the discursive event - the letter Fear Dilma, released to the press on December 7, 2015 and published in its entirety on the G1 News Portal. The study is configured by the procedures adopted as a bibliographic and documentary research, with a qualitative and exploratory approach. The analysis reveals that the letter is a great response, not simply to the immediate interlocutor, Dilma Rousseff, but to Brazilian society, in particular, to voters dissatisfied with the government of the time. Through a speech of victimization, exemption from liability and allegation of competence, the announcer, a public figure representing the second highest official authority in the country, disqualifies and delegitimizes his immediate interlocutor. This study also reveals the power of the theory of discourse genres to understand discursive events emerging from complex societies like ours.